1999
DOI: 10.1117/12.373516
|View full text |Cite
|
Sign up to set email alerts
|

<title>Characterizing user access to videos on the World Wide Web</title>

Abstract: Despite evidence of rising popularity of video on the web (or VOW), little is known about how users access video. However, such a characterization can greatly benefit the design of multimedia systems such as web video proxies and VOW servers. Hence, this paper presents an analysis of trace data obtained from an ongoing VOW experiment in Luleå University of Technology, Sweden. This experiment is unique as video material is distributed over a high bandwidth network allowing users to make access decisions without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 7 publications
3
97
3
Order By: Relevance
“…Acharya et al [3] characterized user access to video objects on the Web and found that half of the requests were for a partial access of the object, indicating early stoppage of transfers by users. Costa et al [11] analyzed workloads from two media servers.…”
Section: Related Workmentioning
confidence: 99%
“…Acharya et al [3] characterized user access to video objects on the Web and found that half of the requests were for a partial access of the object, indicating early stoppage of transfers by users. Costa et al [11] analyzed workloads from two media servers.…”
Section: Related Workmentioning
confidence: 99%
“…Acharya et al [4] presented some basic properties on the internal popularity distribution of streaming media. They found that not all of the requests for streaming media completed the playback.…”
Section: Related Workmentioning
confidence: 99%
“…There exists extensive research in the area of streaming media workload [4] [5] [6] because of its significance on proxy caching, multicast delivery and network management etc. However, relatively few of these studies are on modeling the internal popularity distribution.…”
Section: Related Workmentioning
confidence: 99%
“…These problems and limitations have considerably affected user viewing experience and wasted network resources. A recent study [2] reports that almost half of the video requests stopped during near the beginning of the playback. This result indicates that an improved video delivery scheme needs to be developed to manage the user video browsing behavior.…”
Section: Introductionmentioning
confidence: 99%